Governance as integrity: the case of the internal oversight at the United Nations through the lens of public and private bureacracies transaction cost economics - Da Veiga, M. R.; Major, M. (Journal of Public Budgeting, Accounting and Financial Management, 2019)
Purpose: Through a case study on the governance structures of the UN, the purpose of this paper is to develop a critique of Public and Private Bureaucracies Transaction Cost Economics (PPBTCE) (Williamson, 1999) as a theoretical lens to analyze internal oversight structures. Design/methodology/approach: The authors explore “probity” and “independence” transactions’ attributes through historical narrative case-based research to answer the question – Why did numerous attempts to strengthen the governance of UN internal oversight structures not relieve “probity” hazards? Findings: The analysis shows that at the UN increasing and strengthening the governance of oversight structures, i.e., incentives, did not relieve probity/ethics hazards as predicted in PPBTCE. Secretaries-General and UN General Assembly, entities charged with oversight powers, systematically trumpeted the UN Charter, breaching probity/ethics and disregarding the supervisory independence prerogative of internal oversight structures, hence failing to contribute to the “common good” and to protect the UN mission. Originality/value: This paper is the first application of PPBTCE to internal oversight transactions within an International organization context testing probity and independence attributes. The authors find that “independence” outweighs the “asset specificity” attribute whenever decisions on the governance of internal oversight arise. As far as sourcing decisions are concerned, the authority of the sovereign and the independence of the judiciary as well as quasi-judiciary transactions are not transferable attributes and, thus, cannot be contracted along with the actors’ ethics. PPBTCE should be modified to include, e.g. “virtues ethics” behavioral assumption as a transaction costs’ reduction device and explanatory framework for “probity” hazards, abandoning the opportunism behavioral assumption.